A Statistical Quality Control Study of Wire Rope Corporation of the Philippines, Inc. - Falcis, Charlene Therese M. (College of Engineering, 2002)
Wire Rope Company of the Philippines (WRCP)is a well-known manufacture of wore rope and wire products.Through interviews with plant personnel,identification of the plant's monthly cost,and Pareto analysis,three main quality problems were identified in WRCP manufacturing operations.They were (a)high variability of tensile strenght of Blue Strands wire rope (b)occurrence of rust on 0.5% of raw materials in stock (c)wire breakage during winding.These problems were analyzed using the various tools of statistical process control including control charting for variable and attributes;process capability analysis;and acceptance sampling analysis.It was discovered that the processes involved were capable of meeting industry specifications,but were statistically out-control,which caused these problems.Some recommendations were made to provide solutions.These include the establishment of a product line for Extra Improved Plow Steel wire rope;the adoption of new acceptance sampling plans for raw materials and finished products (ANSI/ASQC Z1.9);regular oiling of raw materials;the construction of an outer covering for the racks;and the hiring of an additional worker for winding.The group also recommends implementing statistical process control in order for the plant personnel to monitor the various manufacturing processes and to detect potential quality problems as early as possible for quick prevention.